Introdução à teoria da medida e integração - Maekawa, Lucas Hideo (Universidade Federal de São Carlos, 2022)
The Lebesgue measure is an important concept with applications in the Lebesgue integral, in the axiomatization of probabilities, and in the definion of integral of spaces more general than the euclidian spaces. This essay presents an introductory study in σ-algebras, measures, exterior measures, the Lebesgue measure, and integrals.
Introduction to measure theory and integration
Keywords: Teoria da medida; Integral; Medida; Medida de Lebesgue; Measure theory; Measure; Lebesgue measure; CIENCIAS EXATAS E DA TERRA::MATEMATICA